On Pairwise Semi-p-separation Axioms in Bitopological Spaces - Majeed, R. N. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this paper, we define a new type of pairwise separation axioms called pairwise semi-p- separation axioms in bitopological spaces, also we study some properties of these spaces and relationships of each one with the ordinary separation axioms in the bitopological spaces.